To solve for v, we will isolate v on one side of the equation.
First, we will multiply both sides of the equation by -1 to eliminate the fraction:
v/ –1 * -1 = -2 * -1
v = 2
Therefore, v = 2.
Solve for v. v/ –1 = –2 v =
11 answers
Solve for q.
q
–4
= –3
q =
q
–4
= –3
q =
To solve for q, we will isolate q on one side of the equation.
First, we will multiply both sides of the equation by -4 to eliminate the fraction:
q/ -4 * -4 = -3 * -4
q = 12
Therefore, q = 12.
First, we will multiply both sides of the equation by -4 to eliminate the fraction:
q/ -4 * -4 = -3 * -4
q = 12
Therefore, q = 12.
Solve for h.
h
–3
= 4
h =
h
–3
= 4
h =
To solve for h, we will isolate h on one side of the equation.
First, we will multiply both sides of the equation by -3 to eliminate the fraction:
h/ -3 * -3 = 4 * -3
h = -12
Therefore, h = -12.
First, we will multiply both sides of the equation by -3 to eliminate the fraction:
h/ -3 * -3 = 4 * -3
h = -12
Therefore, h = -12.
Solve for z.
–13 = z − 45
z =
–13 = z − 45
z =
To solve for z, we will isolate z on one side of the equation.
First, we will add 45 to both sides of the equation to isolate z:
–13 + 45 = z − 45 + 45
32 = z
Therefore, z = 32.
First, we will add 45 to both sides of the equation to isolate z:
–13 + 45 = z − 45 + 45
32 = z
Therefore, z = 32.
Solve for w. w + 20 = 86 w =
To solve for w, we will isolate w on one side of the equation.
First, we will subtract 20 from both sides of the equation to isolate w:
w + 20 - 20 = 86 - 20
w = 66
Therefore, w = 66.
First, we will subtract 20 from both sides of the equation to isolate w:
w + 20 - 20 = 86 - 20
w = 66
Therefore, w = 66.
Solve for u.
u − 28 = 72
u =
u − 28 = 72
u =
To solve for u, we will isolate u on one side of the equation.
First, we will add 28 to both sides of the equation to isolate u:
u - 28 + 28 = 72 + 28
u = 100
Therefore, u = 100.
First, we will add 28 to both sides of the equation to isolate u:
u - 28 + 28 = 72 + 28
u = 100
Therefore, u = 100.